Wisdom of life in the aphorisms of the thinkers of ancient and New time - Rubanau, Anatoly V. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The ideas about the wisdom of life contained in the aphorisms of thinkers of antiquity and new time are considered. It is shown that the following are related to the main ones: preservation of peace of mind, mastery of one’s desires and passions; life according to the principles: be happy if you want to be; appreciate what you have; change your attitude to life if it is unsatisfying; value and love other people; take labour as a source of joy and pleasure; do not get addicted to feelings of greed and desire for profit.
Keywords: wisdom of life; thinkers of antiquity; thinkers of the New time; aphorisms